The effects of research and development expenditure on long-term stock returns: an analysis of the BRICS nations - Swan, Matthew (Department of Finance and Tax, 2023)
Research and development (R&D) facilitate and drive innovation, which plays a critical role in increasing competitiveness for firms and contributing to economic growth. This study examines a sample of 970 firms from Brazil, Russia, India, China and South Africa (BRICS) between 2007-2020 who increased their R&D expenditure or had an unexpected increase in R&D expenditure from one year to the next. The Fama and French (1993) three factor and Carhart (1997) four factor models are used to assess whether these firms earned abnormal returns in the long run. The study finds that value weighted portfolios of firms that increased their R&D expenditure or experienced unexpected R&D expenditure increases exhibited long term positive abnormal returns. This suggests that investors fail to respond immediately to the good news about R&D, consistent with the phenomenon of investor underreaction, and therefore presents an opportunity for market participants to earn abnormal returns by investing in BRICS companies engaged in R&D.